Intracellular release of PluronicL64 unimers into MCF-7/ADR cells to overcome multidrug resistance by surface-modified PAMAM. Issue 21 (16th May 2017) - Zhang, Mengjun; Jing, Shasha; Zhang, Jie; Zhang, Jiulong; Zang, Xinlong; Qiao, Mingxi; Zhao, Xiuli; Hu, Haiyang; Chen, Dawei
Abstract : Multidrug resistance (MDR) has been a major obstacle to tumor chemotherapy. Abstract : Multidrug resistance (MDR) has been a major obstacle to tumor chemotherapy. Pluronic unimers have been reported to be promising copolymers to reverse MDR, and the intracellular delivery of Pluronic unimers is a problem worth thinking. To exert the excellent reversal effect of Pluronic unimers, DOX-loaded G4.0 PAMAM was modified with PluronicL64 via cis -aconitic acid as a pH-sensitive linkage (PCPAMAM/DOX), which could release DOX and Pluronic unimers into cytoplasm. The Pluronic-modified PAMAM (PCPAMAM) exhibited favorable biocompatibility and pH-sensitivity. PCPAMAM/DOX showed a nano-scale size and a sustained in vitro release profile. Compared with a control formulation, PCPAMAM/DOX showed a higher reversal effect on MCF-7/ADR cells and enhanced intracellular drug accumulation. The results of P-gp activity, subcellular distribution of PluronicL64, the ATP level and mitochondrial transmembrane potential all illustrated that free Pluronic unimers could be released by PCPAMAM functioning as reversal agents. In conclusion, PCPAMAM could be a promising vehicle to enhance DOX accumulation by overcoming MDR in MCF-7/ADR cells. This work also provided an effective method to deliver Pluronic unimers into MDR cells.